A Cobalt Catalyst Permits the Direct Hydrogenative Synthesis of 1H‐Perimidines from a Dinitroarene and an Aldehyde. Issue 13 (2nd May 2019) - Schwob, Tobias; Ade, Mirco; Kempe, Rhett
Abstract: A new sustainable catalytic reaction, the synthesis of 1 H ‐ perimidines from a dinitroarene and an aldehyde in the presence of H2, was achieved. An earth‐abundant metal catalyst was developed to permit the efficient, highly chemoselective, and consecutive hydrogenation of dinitroarenes. The catalyst was reusable and easy to handle. The use of a specific Co complex and its pyrolysis at a certain temperature was crucial to achieve high activity for the complex organic transformation. Benzylic and aliphatic aldehydes could undergo the hydrogenative condensation, and many functional groups, including hydrogenation‐sensitive examples such as iodo aryl, nitrile, olefin, and alkyne groups, were tolerated. Abstract : Hydrogenative "Co‐ndensation" : A reusable and nanostructured Co catalyst, synthesized from a specific Co complex and activated charcoal through pyrolysis, mediates the selective and consecutive hydrogenation of dinitroarenes and thus permits the direct synthesis of 1 H ‐perimidines.